Experimental investigation of friction reducer effects on the microstructure and permeability of Longmaxi formation gas shale - Zhonghua Liu; Ye Zhang; Xinfang Ma; Xiangjie Man; Xiaochang Tong; Xiaohui Xie; Yuedi Wang; Zhongpei Ding; Yiqiang Pan; Shunpeng Zeng (Scientific Reports)
Abstract This study proposes a novel method to investigate the effects of friction reducers on the microstructure and permeability of gas shale, using the Longmaxi formation as a case study. By combining high-pressure mercury injection (HPMI) data, the pore size distributions (PSDs) and permeability of gas shale sample were derived from low-field nuclear magnetic resonance (NMR) T 2 spectra under various immersion time conditions. The results demonstrate that this method effectively illustrates the impact of friction reducer on gas shale microstructure across different immersion durations. The proportions of both micro- and macro-pores increase initially, then decrease, and eventually stabilize, peaking at 1 day. Meso-pores follow a different trend, with the maximum occurring at 5 days. Permeability trends correspond with micro- and macro- pore changes, and the permeability ratio remains above 1.0, confirming enhanced permeability. These findings provide insight into optimizing friction reducer formulations and improving shale gas extraction efficiency.